PENGENALAN RESERVASI ONLINE DENGAN MENGGUNAKAN PLATFORM CHECK 24 - Maruanaya, Rita Fransina; Soumokil, Piet; Karuna, Kalvin (Universitas Pattimura, 2025)
This Community Service activity aims to introduce students in the German Language Education Study Program with online reservations using the Check 24 platform, a prominent online service in Germany. This activity addresses the requirements of the tourism industry's workforce, specifically in online reservation tasks, which are expanding in tandem with advancements in digital technology and social demands. Future graduates must possess digital abilities, particularly knowledge, comprehension, and proficiency in utilising online platforms. This exercise employs the Experiential Learning technique, which prioritises direct experience as the fundamental source of learning. This method comprises many stages: 1) Introduction to the content, 2) Concrete experience, and 3) Reflection on the experience. The activity's results indicate that the 10 participants possess not only the capability to utilise the Check 24 platform effectively but also the intrinsic drive for independent and proactive learning, as well as self-development in line with the demands of the labour market, particularly within the tourist sector.